If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2ln(x + 3) = 4 Reorder the terms: 2ln(3 + x) = 4 (3 * 2ln + x * 2ln) = 4 (6ln + 2lnx) = 4 Solving 6ln + 2lnx = 4 Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Reorder the terms: -4 + 6ln + 2lnx = 4 + -4 Combine like terms: 4 + -4 = 0 -4 + 6ln + 2lnx = 0 Factor out the Greatest Common Factor (GCF), '2'. 2(-2 + 3ln + lnx) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-2 + 3ln + lnx)' equal to zero and attempt to solve: Simplifying -2 + 3ln + lnx = 0 Solving -2 + 3ln + lnx = 0 Move all terms containing l to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 3ln + 2 + lnx = 0 + 2 Reorder the terms: -2 + 2 + 3ln + lnx = 0 + 2 Combine like terms: -2 + 2 = 0 0 + 3ln + lnx = 0 + 2 3ln + lnx = 0 + 2 Combine like terms: 0 + 2 = 2 3ln + lnx = 2 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| (7t-2)-(-3+1)=-3(1+3t) | | X+21=4x+4 | | (7d-7)+2= | | 4+5x=-3 | | 7a-(1a-8)=1a+3 | | 120=8x+80 | | -3(4x-2)-6=-3(7x+1)-5 | | -25+m=-3(1+7n) | | -2x+4=5x+53 | | -3(2s-1)-3=-3(6s+6)-3 | | 42xy+56x-6y-8=0 | | 9n+-3=7(n+3)+2n | | f(x)=-11.246 | | 6y+4=25 | | X^2=48/16 | | -6v=-7 | | x+2x+3x+4x=132 | | Fg-9h=10jsolv | | Fg-9h=10jsolve | | c(2c+3)+6(2c+3)= | | -3(4s-2)-6=-3(7s+1)-5 | | 7(7x/1) | | f(x)=-27.083x-16.819 | | -2+3x+7-7x=-29 | | 12+x+4x-4+3x+3=180 | | 4n-9n-n= | | 6x-4=26-4x | | 2sin^2x-5sinx-2=0 | | 3/4m=7.5 | | 19x+20+x+10=90 | | x+x+x+x=44 | | 1e+18= |